2008
DOI: 10.1007/s11104-007-9535-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phosphorus mineral source (Al–P or Fe–P) and pH on cluster-root formation and carboxylate exudation in Lupinus albus L.

Abstract: Lupinus albus L. were grown in rhizoboxes containing a soil amended with sparingly available Fe-P or Al-P (100 μg P g −1 soil/resin mixture). Root halves of individual plants were supplied with nutrient solution (minus P) buffered at either pH 5.5 or 7.5, to assess whether the source of mineral-bound P and/or pH influence cluster-root growth and carboxylate exudation. The P-amended soil was mixed 3:1 (w/w) with anion-exchange resins to allow rapid fixation of carboxylates. Treatments lasted 10 weeks. Forty per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 46 publications
3
25
1
Order By: Relevance
“…We believe that there may be two reasons for this: First, Al-P is more soluble than Fe-P. Similar results were reported in other studies, which suggested that because of its poor solubility, Fe-P was less available to a wide range of crops than either Ca-P or Al-P [29,30]. Second, the higher Al concentration resulting from soil acidification under the Al-P treatment might stimulate the release of organic acid anions and indirectly supplement the Al-P nutrition compared to the Fe-P treatment [31,32].…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“…We believe that there may be two reasons for this: First, Al-P is more soluble than Fe-P. Similar results were reported in other studies, which suggested that because of its poor solubility, Fe-P was less available to a wide range of crops than either Ca-P or Al-P [29,30]. Second, the higher Al concentration resulting from soil acidification under the Al-P treatment might stimulate the release of organic acid anions and indirectly supplement the Al-P nutrition compared to the Fe-P treatment [31,32].…”
Section: Figuresupporting
confidence: 86%
“…In some plant species, exudation of carboxylates can release P from sparingly soluble Fe and Al phosphate via ligand exchange or chelation of metal ions [30,42]. Hoffland [13] and Garden et al [43,44] suggested that carboxylates secreted by plant roots in the rhizosphere could increase P availability by mobilizing P from sparingly soluble Ca, Fe, and Al phosphates.…”
Section: Figurementioning
confidence: 99%
“…Ciereszko and Barbachowska (2000) showed that elimination of phosphorus from the culture medium caused a significant increase in sugar content of roots and both young and older leaves of beans (Phaseolus vulgaris L.), as compared to the control, grown on a complete medium. Probably the increased concentration of sugars, in response to water deficit, can determine the carbon reserves in plants, which are used for construction of new tissues when phosphorus is available, but can also lower the osmotic potential in root cells, and in this way it can also affect the ability to take up some mineral salts form the substrate (Zohlen and Tyler 2004;Shane et al 2008). Such conclusions seem to be confirmed by a significant increase in carbon content (%) of roots of R. 'Cunningham's White' and R. 'Catawbiense Grandiflorum' cuttings, grown in the substrate with CaCO 3 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…patterns of cation uptake and ability of plants to accumulate carboxylic acids in root tissue. The acquisition of P of low lability due to exudation of organic acids has been observed in lupin (Lupinus albus L.) by several researchers (Bais, 2006;Bayon et al, 2006;Shane et al, 2008;Wang et al, 2008). Therefore, based on the above results, it can be expected that cultivating crops with different strategies to access soil nutrients over time may alter soil nutrients and acidity attributes, especially under NT system.…”
Section: Introductionmentioning
confidence: 82%